An Intelligent IoT-Based Irrigation System with Fuzzy Logic Control for Orchid Cultivation - Nabilah Farah Rizqika Widodo; I Gede Puja Astawa; Faridatun Nadziroh (The Indonesian Journal of Computer Science, 2026)
Efficient irrigation management is essential in orchid cultivation because orchids are susceptible to environmental factors, especially soil moisture and temperature. This study details the design and implementation of an Internet of Things (IoT)-based intelligent irrigation system for orchids using fuzzy logic control. The system integrates environmental sensors with a microcontroller platform to enable adaptive irrigation decisions in uncertain, dynamic environments. A fuzzy inference mechanism determines optimal irrigation actions, addressing the limitations of fixed-threshold methods. Furthermore, the system features real-time monitoring, enabling users to observe environmental conditions and system status remotely. Experimental results show that the system operates reliably and maintains irrigation conditions within the target range. These findings suggest that the proposed approach offers a practical and effective solution for intelligent irrigation in precision agriculture.